Behaviour of atrazine in brazilian soils under laboratory conditions - Nakagawa, Lia Emi; Luchini, Luis Carlos; Musumeci, Maria Raphaela; de Andréa, Mara Mercedes (Pesquisa Agropecuaria Brasileira, 1995)
The persistence, mobility and adsorption of atrazine in two Brazilian soils (Gley Humic and Deep Red Latosol) were studied in laboratory, for 180 days after 14C-atrazine addition to the soil samples, incubated in the dark at 25 °C. Atrazine had a half-life of 56 days in Humic Gley soil and 54 days in the Deep Red Latosol. Hydroxyatrazine was the main metabolite, detected in higher percentage in the Humic Gley soil; the metabolites deetylatrazine and deisopropylatrazine were also identified, but in lower concentration in both soils. Atrazine adsorption in both soils was similar, K value of 2.6 and 2.1 in the Humic Gley and Deep Red Latosol respectively. After four runs in the soil thin-layer plates atrazine had higher mobility in the Deep Red Latosol (Rf = 0.74) to a Rf = 0.66 in Humic Gley.